Respostas

2014-02-20T20:02:46-03:00
A) -x=-1+4y                                  b) -y=0-3x
     x=1-4y                                         y=3x
subs.                                             subs.
                                         
1-4y+7y=-2                                       -4x+3x=-2
3y=-2-1                                              -x=-2
3y=-3                                                  x=2
y=-1                                             


x+7y=-2                                            3.2-y=0
x-7=-2                                                6-y=0
x=5                                                    -y=-6      y=6
1 5 1
obrigada, agora minha tarefa ta pronta =D
kkkkkkkk